Novel Design of Dual Resonant RF Microstrip Surface Coil for High-Field MR Applications - Adhi Mahendra; Basari; Eko Tjipto Rahardjo (IEEE Access)
Radio Frequency (RF) coils are necessary for MRI machines and are critical in improving image quality. Due to numerous research efforts in RF coil development, birdcage and surface coils are the most commonly used in clinical applications to enhance medical imaging quality. This article introduces a new surface-type RF coil that is improved by its proximity to the scanned object, boosting its effectiveness. Contrary to past research that examined RF coils operating at one resonant frequency, this study presents a microstrip-based surface RF coil created for dual-frequency use at 64 MHz and 128 MHz, matching the Larmor frequencies for 1.5 T and 3 T MRI machines. The coil was carefully planned, tested, and created, with simulations including a human body model to assess the distribution of the $B_{1}$ field and signal-to-noise ratio (SNR), both essential for assessing the RF coil’s performance in the coronal plane. A tuning circuit was created and tested to maximize resonance at specific frequencies. In contrast, a matching circuit was designed to improve power transfer efficiency between the signal generator and the coil. The suggested RF coil was enhanced by incorporating these circuits, improving overall performance. Both the suggested surface-type microstrip RF coil, which includes tuning and matching circuits, effectively functions at 64 MHz and 128 MHz, as shown by both simulation and experimental results, making it a viable clinical option.